DYNAMIC ANALYSES OF SOIL-STRUCTURE INTERACTION IN OFFSHORE WIND TURBINE ON TRIPOD IMPACTED BY A SHIP - HAN ZhiWei; ZHOU HongJie; LI Chun; DING QinWei (Jixie qiangdu)
The probability of collisions between offshore wind turbines and ships increases with the development of offshore wind farm. Based on nonlinear dynamic analysis method,through LS-DYNA to simulate the ship impact a 4 MW offshore wind turbine tripod,the paper compare p-y curve method and fixed bottom end constraint. The author has a comparison and analysis of energy conversion、maximum collision force、relationship of horizontal displacement and depth of soil、contact force、shear force and stress-strain. The results show that energy conversion of the pie column under the p-y curve is faster than that under the fixed bottom end restraint; the bottom end of the steel pipe column is more susceptible to be damaged when a ship impacts offshore wind turbine foundation under the fixed bottom end restraint method; the soil layer is from shallow to deep,in which shallow soil has the most influence on the stability of the pile and the horizontal displacement of three steel column gradually decreases,the improvement of the properties of the shallow soil can effectively improve the safety of the pile; the increase of the ship quality,the contact force and shear force are increasing; the difference in contact force between the curve method and the fixed bottom end constraint increases with the increase of the quality of the ship,and the shear force difference decreases.